Office 365 SharePoint sites - Jesperson, Ryan, Dr.; Safari eBooks ([Place of publication not identified] : Intellezy, 2017)
"This course is an introduction to Office 365 Sites. Upon completion of this course, users will have a basic understanding of Sites, navigation, lists, libraries, searching, newsfeeds, views, permissions, and organization."--Resource description page.
Presenter, Dr. Ryan Jesperson.
Title from title screen (viewed March 13, 2018).
Date of publication from resource description page.
Keywords: Microsoft SharePoint (Electronic resource); Cloud computing; Electronic books